Theorizing the drop in white-collar crime prosecutions: An ecological model - McGrath, Joe (Punishment & society, 2021)
This article theorizes prosecutorial decision-making using an ecological model which proposes that prosecutorial outcomes are shaped by four inter-related and intersecting systems: (a) macro-level, or societal, factors such as crime rates (b) meso- and exo-level factors, such as organisational culture, (c) micro-level factors, such as interactions between prosecutors, and (d) individual-level factors, such as victim and perpetrator characteristics. While the model is designed to explain prosecutorial decision-making in general, it also accounts for the paradoxical trends observed in the US since the financial crash in 2008 when the number of prosecutions fell despite a heating up of political rhetoric around white-collar crime. The utility of the model is explored through a critical reading of the extant literature and an analysis of relevant qualitative and quantitative data. The discussion shows that, while each set of factors shapes prosecutorial outcomes to some extent, two explanations are particularly convincing. First, the data suggest that the dip in prosecutions may be explained by prosecutors focusing limited resources on more serious (albeit fewer) cases. Second, delays in case processing emerged sometime between 2011 and 2012 due to bottlenecks in the criminal justice process and coincided with the fall in prosecutions. While the roles played by some of the factors considered in this article are already well-known, the contributions of systemic delays and the shift towards more resource intensive cases represent new findings.